Minocycline and risperidone prevent microglia activation and rescue behavioral deficits induced by neonatal intrahippocampal injection of lipopolysaccharide in rats. - Furong Zhu; Yingjun Zheng; Yu-qiang Ding; Yong Liu; Xianghui Zhang; Renrong Wu; Xiaofeng Guo; Jingping Zhao (PLoS ONE)
Background Various signs of activation of microglia have been reported in schizophrenia, and it is hypothesized that microglia activation is closely associated with the neuropathology of schizophrenia. Methods Neonatal intrahippocampal injection of lipopolysaccharide (LPS), an activator of microglia, was performed in rats at postnatal day 7 (P7), and they were separately given saline, risperidone (0.5 mg/kg), minocycline (40 mg/kg) or a combination of both of them at P42 for consecutive 14 days. Behavioral changes (locomotion activity, social interaction, novel object recognition and prepulse inhibition) were examined and the number of microglia was assessed by using immunohistochemistry in adulthood. Results The adult rats in LPS-injected group showed obvious behavioral alteration (e. g. deficits in social interaction, novel object recognition and prepulse inhibition) and a dramatic increase of number of activated microglial cells in the hippocampus and other brain regions such as cerebral cortex and thalamus compared to those in saline-injected group. Interestingly, application of either minocycline, risperidone or both of them significantly rescued behavioral deficits and attenuated microglia activation. Conclusion Our results suggest that inhibition of microglia activation may be one of mechanisms underlying the antipsychotic effect of minocycline and risperidone.